2005
DOI: 10.2139/ssrn.850071
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and the Environment: Exploring the Relationship Between Household Incomes, Private Assets, and Natural Assets

Abstract: Using purpose-collected survey data from 537 households in 60 different villages of the Jhabua district of India, this paper investigates the extent to which rural households depend on common-pool natural resources for their daily livelihood. Previous studies have found that resource dependencedefined as the fraction of total income derived from common-pool resources-strongly decreases with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 10 publications
(11 reference statements)
2
19
0
1
Order By: Relevance
“…2000;Adhikari, 2005;and Narian et al, 2005). Cavendish (2000) argues that actual household income is usually underestimated, because household income measurements usually omit benefits generated from freely extracted goods and services from common pool natural resources.…”
Section: Resource Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…2000;Adhikari, 2005;and Narian et al, 2005). Cavendish (2000) argues that actual household income is usually underestimated, because household income measurements usually omit benefits generated from freely extracted goods and services from common pool natural resources.…”
Section: Resource Dependencymentioning
confidence: 99%
“…resource dependency declines after a threshold value of income. Furthermore, based on a study of forest dependency in rural India, Narian et al (2005) argue that the relationship between resource use and the wealth of households is more complicated. In particular, for households that extract positive amounts of the CPNRs, the dependency follows a U-shaped relationship with income.…”
Section: Resource Dependencymentioning
confidence: 99%
“…Also, there had been frequently burning of existing larger plantations and this was associated with the increasing scarcity in land ownership by the villagers. The same argument had been canvassed by Narain et al [19] who found that households with less land tend to perceive conservation programmes as a limitation to their subsistence needs and therefore are likely to have negative attitude toward conservation. Masozera [20], Reardon and Vostii [21] Chemicals.…”
Section: Size Of Land Owned By the Villagersmentioning
confidence: 70%
“…In sub-Saharan Africa, for example, where perhaps 90 percent of the population relies on woodfuels for cooking (GEF 2013;IEA, 2006), the use of charcoal as a cooking fuel is still increasing rapidly, with the value of the charcoal industry there estimated at USD 8 billion in 2007(World Bank, 2011. In Asia, even better-off rural households have often been observed to be highly dependent on woodfuels, as found by Narain et al (2005) for India, the Government of Nepal (GN, 2004) for Nepal, and Chaudhuri and Pfaff (2002) for Pakistan. With the volatile and often high price of "modern" energy sources, this situation is unlikely to change for some time, a fact often neglected in policy discussions on "energy futures" in low-income nations, which place unrealistic emphasis on "more modern" energy sources, rather than attempting to make woodfuel production and use more efficient and sustainable (Iiyama et al, 2014a;Schure et al, 2013).…”
Section: 2mentioning
confidence: 99%